ANTIOXIDANT AND FREE RADICAL SCAVENGING ACTIVITIES OF EDIBLE WEEDS - Kumar, S.; Kumar, D. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Chenopodium album and Vitis trifolia are widely growing weeds in India. These are nutritious and eaten as food or vegetable. Preliminary phytochemical screening of these plants showed the presence of high amount of phenolics and flavonoids. Subsequent quantification showed the presence of 0.94% w/w phenolics (calculated as gallic acid) and 0.27 % w/w flavonoids calculated as catechin equivalents per 100 g of fresh mass of C. album leaf extract whereas V. trifolia was found to contain 1.23 % of gallic acid equivalents of phenolic compounds and total flavonoid content was 0.38 % of catechin equivalent per 100 g of fresh mass. The presence of phenolic compounds prompted us to evaluate its antioxidant activity. Both plants were screened for antioxidant potential by using various in vitro methods at different concentration (250–2500 ïg/ml). Aqueous leaf extract of C. album showed free radical scavenging effect on the DPPH, superoxide anion, hydroxyl radicals, nitric oxide production and hydrogen peroxide radicals as 86.42Â±2.8, 75.24Â±3.8, 78.54Â±3.7, 74.38Â±4.2 and 74.23Â±3.5 % respectively at a concentration of 2500 Î¼g/ml. Methanolic fruit extract of V. trifolia exhibited significant reducing power and free radical scavenging effect on DPPH, superoxide anion, hydroxyl radicals, nitric oxide production and hydrogen peroxide radicals as 89.15Â±3.7, 79.71Â±3.4, 81.27Â±3.2, 76.83Â±2.7 and 80.37Â±4.2% respectively. All these antioxidant activities were concentration dependent which were compared with standard antioxidants such as BHA, Î±-tocopherol and ascorbic acid.